2005
DOI: 10.1098/rsbl.2005.0336
|View full text |Cite
|
Sign up to set email alerts
|

Avian collision risk at an offshore wind farm

Abstract: We have been the first to investigate whether long-lived geese and ducks can detect and avoid a large offshore wind farm by tracking their diurnal migration patterns with radar. We found that the percentage of flocks entering the wind farm area decreased significantly (by a factor 4.5) from pre-construction to initial operation. At night, migrating flocks were more prone to enter the wind farm but counteracted the higher risk of collision in the dark by increasing their distance from individual turbines and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
194
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(197 citation statements)
references
References 5 publications
1
194
0
2
Order By: Relevance
“…Wind energy is a recent phenomenon and only a few studies have been conducted regarding offshore wind parks (Larsson 1994;Guillemette, Larsen & Clausager 1998;Guillemette & Larsen 2002;Desholm & Kalhert 2005). Many studies have addressed the possible impacts on birds of onshore wind parks (reviewed by Langston & Pullan 2003) but the findings from these studies cannot simply be extended to an offshore scenario because different species will be impacted.…”
Section: Introductionmentioning
confidence: 99%
“…Wind energy is a recent phenomenon and only a few studies have been conducted regarding offshore wind parks (Larsson 1994;Guillemette, Larsen & Clausager 1998;Guillemette & Larsen 2002;Desholm & Kalhert 2005). Many studies have addressed the possible impacts on birds of onshore wind parks (reviewed by Langston & Pullan 2003) but the findings from these studies cannot simply be extended to an offshore scenario because different species will be impacted.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that the environmental effects of properly sited, executed, and operated wind projects are, as a general rule, low level (18). For example, fatality rates of birds are lower than might have been anticipated given avoidance behavior (19), and impacts on dolphins and porpoises have been identified as being more of a short-term nature than resulting in long-term consequences (20)(21)(22). In light of the European findings, and given that electricity generated by wind power displaces fossil fuel generation (23), it is perhaps unsurprising that organizations, such as the National Wildlife Federation and Massachusetts Audubon, support offshore wind power.…”
Section: Research Requiredmentioning
confidence: 99%
“…Radar studies undertaken at several offshore wind farms document a substantial avian avoidance response, with the birds modifying their flight trajectories to avoid the turbines and therefore reducing the risk of collision [43] (see Figure 3). Species such as common eider Somateria mollissima modified their flight trajectories at an average distance of 3km from the Nysted offshore wind farm (Denmark) during daylight (less by night) compared to pre-construction flight patterns [43,44].…”
Section: Sea Birdsmentioning
confidence: 99%
“…Species such as common eider Somateria mollissima modified their flight trajectories at an average distance of 3km from the Nysted offshore wind farm (Denmark) during daylight (less by night) compared to pre-construction flight patterns [43,44]. At the Tunø Knob offshore wind park in the Kattergat (Denmark), Larsen and Guillemette [45] found that common eiders mostly avoided flying close to and within the wind park and that this avoidance was caused not by the action of the rotors but by the presence of the turbine structure themselves.…”
Section: Sea Birdsmentioning
confidence: 99%